Financial hardship after cancer: revision of a conceptual model and development of patient-reported outcome measures - Salene MW Jones; Jean Yi; Nora B Henrikson; Laura Panattoni; Veena Shankaran (Future Science OA, 2024)
Aim: This qualitative study refined a conceptual model of financial hardship and developed measures corresponding to model constructs. Methods: Eighteen women with breast cancer recruited through a comprehensive cancer center completed interviews. A qualitative framework analysis was conducted of the interviews. Results: Participants experienced varying levels of financial hardship. Protective factors included good health insurance, work accommodations and social support. Participants worried about cancer care costs and employment. Programs for alleviating financial hardship had high administrative burdens. Four preliminary financial hardship measures were developed: coping, impacts, depression and worry. Conclusion: Reducing administrative barriers to benefits could reduce financial hardship after cancer. More research is needed on the effects of out-of-network/formulary care and denials of coverage and to validate the measures.